Teaching Competence and Adversity Quotient of Teachers in Alternative Learning System (ALS) and Students’ Learning Engagement in The City Schools Division Offices in the Province of Laguna - Parto, Laurence E.; Yango, Antonio R. (Technium Social Sciences Journal, 2023)
This study attempted to determine the ALS teachers’ teaching competence and adversity quotient as predictors of students’ learning engagement in the city schools division offices in the Province of Laguna. Specifically, it investigated the respondents’ level of teaching competence in terms of content knowledge and pedagogy, learning environment, diversity of learners, curriculum and planning, community linkages and professional engagement and professional growth and professional development; respondents’ level of adversity quotient and its dimensions; control, ownership, reach and endurance, and level of students’ learning engagement. The findings showed that the overall weighted mean of 3.64 revealed that the ALS teachers’ teaching competence was very high; while the overall weighted mean of 2.76 revealed that the respondents’ AQ level was high. Moreover, the findings showed that the average weighted mean of 3.31 revealed that the level of the students’ learning engagement was very high. Meanwhile, the findings showed that the relationship between the respondents’ level of teaching competence and level of adversity quotient were all greater than the 0.01 significance level. Therefore, there was no significant relationship between the ALS teachers’ teaching competence and their level of adversity quotient was observed. In addition, the finding showed that the relationship between the respondents’ teaching competence and students’ learning engagement were less than the test of significance at 0.01 leading to the rejection of the null hypotheses. This showed that there was a significant relationship between the respondents’ teaching competence and student learning engagement. Lastly, the relationship between the respondents’ level of adversity quotient and level of students’ learning engagement were higher than the test of significance at 0.01 leading to the acceptance of the null hypotheses. This shows that there was no relationship between the respondents’ level of adversity quotient and the level of student learning engagement.